Variable Pay and Work Hours: Does Performance Pay Reduce the Gender Time Gap? - Mehrzad B. Baktash; John S. Heywood; Uwe Jirjahn (Global Labor Organization (GLO), 2024)
Using German survey data, we show that performance pay is associated with a substantially lower gender hours gap. While performance pay increases the work hours of both men and women, the increase is much larger for women than for men. This finding persists in worker fixed effects estimates. We argue our finding likely reflects differences in household production and specialization by gender. Thus, we show that performance pay is not associated with increased hours for men with children in the household. Yet, performance pay is associated with a very large increase in hours for women with children in the household.
Keywords: D10; J22; J33; M52; 330; Performance Pay; Contracted Hours; Actual Hours; Gender